The role of agriculture in economic development in Somalia - Abdullahi Mohamud, Yasmin; Marof, Aini Azeqa; Mohamed, Abdullahi Mohamud; Mohamed Ali, Abdullahi (Human Resource Management Academic Research Society, 2023)
This study investigates the relationship between agriculture and economic growth in Somalia over the period from 1980 to 2020. The research objectives encompassed describing the role of agriculture employment, agriculture exports, and crop production in contributing to economic development during the specified time frame. To achieve these objectives, the study employed the Autoregressive Distributed Lag (ARDL) model, a form of regression analysis that utilizes historical data to identify relationships between variables. The dependent variable chosen to represent economic development was the Gross Domestic Product (GDP), while the independent variables included the agriculture employment rate, agriculture exports, and crop production. Data analysis was performed using E-views software, and descriptive statistics and graphical representations were utilized to present the findings effectively. Secondary data were sourced from reputable institutions such as the World Bank, International Monetary Fund (IMF), and the Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC) for the extensive period from 1980 to 2020. The results revealed a positive relationship between the agricultural sector and Somalia's GDP, indicating that an increase in agricultural activities positively impacted the country's economic growth. These findings highlight the significance of agriculture as a driving force behind economic development in Somalia during the examined period. As such, policymakers and stakeholders should consider investing in and promoting the agriculture sector to foster sustainable economic growth in the country.